1979
DOI: 10.1007/bf02277956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on the pollen vitality and yield of rice plants (Oryza sativa L. var. Jaya)

Abstract: SummaryRice plants were grown in sand cultures with nutrient solution including boron at 0, 1, 2.5 and 5 ppm concentrations.In general, supply of boron improved the pollen vitality of rice flowers. It was stimulating up to 2.5 ppm concentration in the nutrient solution, beyond which (i.e., at 5 ppm) inhibitory effects appeared.The availability of boron also increased the yield of rice grains in the same order. Stimulating effects of boron may be linked with greater availability of sugars, increased enzymatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 3 publications
2
15
0
3
Order By: Relevance
“…Rice yield responded to B application due to its positive effect on the number of tillers, panicles, weight of grain and filled grains. These results suggests that B addition improves seed setting due to its major role in many plant physiological functions such as it promotes cell growth and development of the rice panicle (Garg et al, 1979). These findings are consistent with those of Rashid et al (2002) and Dunn et al (2005).…”
Section: Grain Yield Of Ricesupporting
confidence: 85%
“…Rice yield responded to B application due to its positive effect on the number of tillers, panicles, weight of grain and filled grains. These results suggests that B addition improves seed setting due to its major role in many plant physiological functions such as it promotes cell growth and development of the rice panicle (Garg et al, 1979). These findings are consistent with those of Rashid et al (2002) and Dunn et al (2005).…”
Section: Grain Yield Of Ricesupporting
confidence: 85%
“…B was also found to affect fertilization. Garg et al (1979) observed a decrease in grain number per ear in B-deficient rice plants. In B-deficient barley, a total lack of fertilization was also observed (Simojoki 1972).…”
Section: Discussionmentioning
confidence: 92%
“…Under well nitrogen availability, boron has good impact on better development of pollens, pollen germination, anther viability, anthesis, cell division, enhanced enzymatic activity and more availability of sugars (Garge et al, 1979), end resulted in production of more seeds. Transport of photo-assimilates towards achenes was triggered rapidly with nitrogen and boron nutrition management.…”
Section: Discussionmentioning
confidence: 99%